Heme Oxygenase-1 Induction by Carbon Monoxide Releasing Molecule-3 Suppresses Interleukin-1β-Mediated Neuroinflammation - Lin, Chih-Chung; Yang, Chien-Chung; Hsiao, Li-Der; Chen, Ssu-Yu; Yang, Chuen-Mao (Frontiers in Molecular Neuroscience, 2017)
Neurodegenerative disorders and brain damage are initiated by excessive production of reactive oxygen species (ROS), which leads to tissue injury, cellular death, and inflammation. In cellular anti-oxidant systems, heme oxygenase-1 (HO-1) is an oxidative-sensor protein induced by ROS generation or carbon monoxide (CO) release. CO releasing molecules (CORMs), including CORM-3, exert anti-oxidant and anti-inflammatory effects. However, the molecular mechanisms of CORM-3-induced HO-1 expression and protection against IL-1β-induced inflammatory responses have not been fully elucidated in rat brain astrocytes (RBA-1). To study the regulation of CORM-3-induced HO-1 expression, signaling pathways, promoter activity, mRNA, and protein expression were assessed following treatment with pharmacological inhibitors and gene-specific siRNA knockdown. We found that CORM-3 mediated HO-1 induction via transcritional and translational processes. Furthermore, CORM-3-induced HO-1 expression was mediated by phosphorylation of several protein kinases, such as c-Src, Pyk2, protein kinase C (PKC)α, and p42/p44 mitogen-activated protein kinase (MAPK), which were inhibited by respective pharmacological inhibitors or by gene-specific knockdown with siRNA transfections. Next, we found that CORM-3 sequentially activated the c-Src/Pyk2/PKCα/p42/p44 MAPK pathway, thereby up-regulating mRNA for the activator protein (AP)-1 components c-Jun and c-Fos; these effects were attenuated by an AP-1 inhibitor (Tanshinone IIA) and other relevant inhibitors. Moreover, CORM-3-induced upregulation of HO-1 attenuated the interleukin-1β-induced cell migration and matrix metallopeptidase-9 mRNA expression in RBA-1 cells. These effects were reversed by an MMP2/9 inhibitor or by transfection with HO-1 siRNA.